Exploring New Intermediaries in the Labour Market - Nesheim, Torstein; Jesnes, Kristin (Relations industrielles / Industrial Relations, 2022)
New labour market intermediaries, such as those using digital platforms, are challenging not only temporary help agencies but also traditional employer–employee relationships. A new conceptual scheme is proposed to distinguish between three functions: a) allocating the work; b) entering into a contract with the worker; and c) managing and organizing the work.By using this scheme in a study of 11 intermediaries of knowledge-intensive work in Norway, we found that self-service platforms are insufficient and must be supplemented with active client involvement during several stages of the allocation process. Such active involvement is driven by the complexity of the assignments and the client’s uncertainty about job requirements. Regarding management of the work, our findings contrast both with the common perception of independent contractors’ work as self-directed and with the idea that an intermediary can use algorithms to manage work. In reality, the contractor's work is managed in very different ways.Our paper outlines several approaches that combine some or all of the three functions and adds to the literature by describing new forms of triangular work arrangements.